The Influence Of Emotional Intelligence On The Performance Strategy Of Playing Soccer Athletes Aged 14 - 17 Years - Arpandi, Mihdan; Subarjah, Herman; Paramitha, Sandey Tantra (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Athletes often experience high emotional fluctuations both in and out of competition, which are related to their performance. This study aims to determine the effect of emotional intelligence on the performance strategy of playing soccer athletes aged 14-17 years. This type of research is descriptive quantitative with questionnaire tools. This research was conducted at SSB Prahara and SSB BBS. The sampling technique in this study was non probability sampling, with purposive sampling method. The sample used in this study amounted to 60 people. The data analysis technique in this study used simple linear regression analysis techniques. Based on the results obtained from the research, the results of simple linear regression analysis and the coefficient of determination between emotional intelligence on the performance strategy of playing soccer athletes aged 14-17 years show a small but significant influence, with a significance value of 0.000 which means P 0.05 and R Square of 21.7%. Coaching emotional intelligence in athletes aged 14-17 years can be a key factor in improving performance. Emphasis on this aspect should be an integral part of the sports training approach at this age.